The Journey of Organizing and Empowering Yolanda Affected Community: Experiences from a Post Disaster Housing Project in Javier, Leyte, Philippines - Geges, Dhino B; Faulmino, Chrislyn Joanna P. (Advances in Social Sciences Research Journal, 2017)
The study was conducted to assess the journey of organizing and empowering Haiyan-affected community who was beneficiary of a housing project. Specifically, the study sought to (a) characterize the socio-demographic characteristics of project beneficiaries; (b) determine the roles and contributions of the training participants in the various phases of the housing project; (c) identify support mechanisms of family members on the training participants; (d) discuss the enabling and restraining factors affecting the organizing efforts experienced by the project; and (e) recommend plans for further enhancement of family participation anchored to the community organizing perspective. The data collection involved community immersion, key informant interviews, and survey. Data were analyzed using descriptive statistics and grounded analysis of qualitative data. It was revealed that most of the respondents were married and had reached high school level of education. Poverty incidence is relatively high since the average household monthly income fell between PHP 1,800-3,600.00. In terms of livelihood, construction and agriculture-related activities were the most common jobs for men, while women were mostly engaged in service-oriented jobs and community volunteerism. Proactive engagement to organizational development-related trainings was recognized as the key role of the majority of the mothers as their husbands and sons participated in the Galing Mason training, a masonry skills enhancement program of Holcim Philippines Inc. In terms of family support, mothers and wives were identified as source of encouragement while fathers or male members of the family provided transport services to assist on the training needs and preparation. Institutional support coming from public and private organizations, high social acceptability, family support system, and improved social capital were also instrumental in accomplishing organizing work and empowerment activities toward resiliency.